Functional Assessment of Ahmad Yani Road as an Urban and Tourism Corridor - Hadi, Suprapto; Dahlan, Mochammad Affan; Indriani, Agustin Ratna; Maulana, Fajar Firdaus; Hayati, Reffi Nur (Civil and Sustainable Urban Engineering, 2026)
Ahmad Yani Road stood as a vital artery in Tegal City, bridging the gap between urban centers and local tourism landmarks. While its administrative label defined it as an urban road, the street’s physical evolution told a different story one centered on pedestrians and tourism. Rather than accepting the status quo, this study examined the functional disconnect of Ahmad Yani Road by integrating three distinct approaches: geometric audits, traffic flow metrics, and road safety inspections (RSI). The fieldwork was conducted using a descriptive comparative framework, with data collection covering physical lane measurements, visual documentation, and traffic counts. These data were evaluated against a combination of Bina Marga’s local regulations and international benchmarks for walkable tourism streets. The findings revealed a substantial performance gap. The corridor failed to adequately fulfill its function as an urban road, meeting only 57.14% of the requirements due to narrow lanes and insufficient safety infrastructure. However, when assessed as a tourism corridor, the results were markedly different, with the road achieving 90% compliance, supported by its active frontage and pedestrian-oriented design. Although traffic flow remained relatively stable (DS = 0.66, LOS C), an underlying vulnerability persisted. The corridor operated near a critical threshold, where sudden increases in tourist activity or roadside disturbances could have disrupted traffic movement. Ultimately, Ahmad Yani Road had evolved beyond its original administrative classification, and the findings supported the need for a policy shift toward adaptive management to safeguard its emerging role as a vibrant public space.